Quasi-Contextualized Speech Treatment in Traumatic Brain Injury Inpatient Rehabilitation: Effects on Outcomes During the First Year After Discharge. Issue 5 (September 2021) - Beaulieu, Cynthia L.; Peng, Juan; Hade, Erinn M.; Montgomery, Erin; Gilchrist, Kamie; Corrigan, John D.; Horn, Susan D.; Bogner, Jennifer
Abstract : Objective: To evaluate the effect of providing quasi-contextualized speech therapy, defined as metacognitive, compensatory, or strategy training applied to cognitive and language impairments to facilitate the performance of future real-life activities, on functional outcomes up to 1 year following traumatic brain injury (TBI). Setting: Acute inpatient rehabilitation. Participants: Patients enrolled during the TBI-Practice-Based Evidence (TBI-PBE) study ( n = 1760), aged 14 years or older, who sustained a severe, moderate, or complicated mild TBI, received speech therapy in acute inpatient rehabilitation at one of 9 US sites, and consented to follow-up 3 and 9 months postdischarge from inpatient rehabilitation. Design: Propensity score methods applied to a database consisting of multisite, prospective, longitudinal observational data. Main Measures: Participation Assessment with Recombined Tools-Objective-17, FIM Motor and Cognitive scores, Satisfaction With Life Scale, and Patient Health Questionnaire-9. Results: When at least 5% of therapy time employed quasi-contextualized treatment, participants reported better community participation during the year following discharge. Quasi-contextualized treatment was also associated with better motor and cognitive function at discharge and during the year after discharge. The benefit, however, may be dependent upon a balance of rehabilitation time that relied on contextualized treatment. Conclusions: The use of quasi-contextualized treatment may improve outcomes. Care should be taken, however, to not provide quasi-contextualized treatment at the expense of contextualized treatment. Abstract : Supplemental Digital Content is Available in the Text.